Analysis and Functional Significance of TRAP1 in Glioblastoma - I. F. Gareev; O.A. Beylerli; Zhang Hongli; S. A. Roumiantsev (Креативная хирургия и онкология, 2025)
Introduction. Glioblastoma exhibits high aggressiveness and complex mechanisms of therapy resistance. Tumor necrosis factor receptor-associated protein 1 (TRAP1) participates in metabolic regulation and tumor cell resistance to apoptosis; however, its role in glioblastoma remains understudied. Materials and methods. Glioma cell lines T98G and human brain astrocytes (HBA) were used as controls. TRAP1 expression was suppressed via the lentiviral transduction method using short hairpin RNA (shRNA). Exosomes were isolated from culture medium by ultracentrifugation and subsequently identified by typical markers (TSG101, CD63, and ALIX). The protein-level expression of TRAP1 and key glycolytic enzymes was analyzed by western blot analysis. Cell viability was assessed using the MTT assay, while apoptosis levels were measured using Annexin V-FITC/PI staining. In addition, ATP production was analyzed using bioluminescent methods. Results and discussion. TRAP1 was overexpressed in T98G cells, including in exosomes, while HBA exhibited moderate to low TRAP1 levels. The suppression of TRAP1 in T98G cells resulted in a decrease in glycolytic enzyme expression, an increase in apoptosis, and a decrease in cell viability. TRAP1 overexpression facilitated metabolic reprogramming toward aerobic glycolysis, along with reducing ATP synthesis. Exosomal TRAP1 likely participates in intercellular communication, promoting tumor adaptation to stress and the formation of a pro-tumor microenvironment. Conclusion. These findings support the pivotal role of TRAP1 in regulating metabolic status and maintaining aggressive phenotypes in glioblastoma. The targeted inhibition of TRAP1 may become a promising therapeutic strategy for glioblastoma, aimed at reducing tumor cell viability and limiting metabolic flexibility.